Ciluba Speaking Learners’ Interference in Sound Production (International Journal of Scientific Research and Management (IJSRM), 2024)
This study addresses interference produced by Cilubà speaking learners in their English learning process in the classroom (in some schools of Mbujimayi). It aims at providing some hints which are likely to help overcome such difficulties of language learners use English with some connected speech sounds. Observation and questionnaires (interviews) are approaches used to collect and interpret the data. After investigation, the study has proved that there are three types of sounds interference learners’ levels, namely grouped as Higher interference users (75% of 80 learners observed); Intermediate level learners (36% of 125 learners observed); and Advanced level learners (25% of 42 learners observed). Some remedies should be taken into consideration like, intensification of reading tasks, the allotment of more time to oral tasks than to written ones by making learners talk more and more, the focus on learners’ pronunciation problems for some items containing complex vowel sounds, training learners how to discriminate sounds they cross enough difficulties, and helping them to have more practice on spelling exercises.